2023
DOI: 10.2147/dddt.s413897
|View full text |Cite
|
Sign up to set email alerts
|

Jiawei Danxuan Koukang Alleviates Arecoline Induced Oral Mucosal Lesions: Network Pharmacology and the Combined Ultra-High Performance Liquid Chromatography (UPLC) and Mass Spectrometry (MS)

Linghang Zhou,
Jin Tan,
Yuzhe Dai
et al.

Abstract: Purpose Arecoline is one of the main toxic components of arecoline to cause oral mucosal lesions or canceration, which seriously affects the survival and life quality of patients. This study analyzed the mechanism of Jiawei Danxuan Koukang (JDK) in alleviating arecoline induced oral mucosal lesions, to provide new insights for the treatment of oral submucosal fibrosis (OSF) or cancerosis. Methods Metabolomics was applied to analyze the composition of JDK and serum metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(65 reference statements)
1
0
0
Order By: Relevance
“…Therefore, we used immunohistochemical staining and flow cytometry to observe the changes in Th17 cells in each group to explore whether QU interferes with Th17 cells. The results showed that, compared with that in the control group, the number of Th17 cells in the periodontitis group increased but decreased significantly after intragastric administration of QU, which is consistent with previous reports that QU inhibits Th17 cell differentiation and reduces inflammation to improve disease progression [ [34] , [35] , [36] ]. In mice with allergic rhinitis, QU was found to improve rhinitis symptoms by reducing the percentage of Th17 cells and inhibiting the expression of inflammation-related factors [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we used immunohistochemical staining and flow cytometry to observe the changes in Th17 cells in each group to explore whether QU interferes with Th17 cells. The results showed that, compared with that in the control group, the number of Th17 cells in the periodontitis group increased but decreased significantly after intragastric administration of QU, which is consistent with previous reports that QU inhibits Th17 cell differentiation and reduces inflammation to improve disease progression [ [34] , [35] , [36] ]. In mice with allergic rhinitis, QU was found to improve rhinitis symptoms by reducing the percentage of Th17 cells and inhibiting the expression of inflammation-related factors [ 37 ].…”
Section: Discussionsupporting
confidence: 91%